Determination of the population genetic structure of Miniopterus schreibersii in the Anatolian transition zone - Çoraman, Emrah. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2008., 2008)
Populations and species boundaries of Miniopterus schreibersii were investigated in Thrace and central Anatolia, using the sequenced segments of a mitochondrial DNA control region. Analyses confirmed the presence of two distinct forms of M. schreibersii, namely M. s. schreibersii and M. s. pallidus. The results showed that the forms separated approximately 750,000 years before present and underwent the subsequent expansions of their populations. The percent of genetic variance among clades was very high compared to variances within the clades, indicating a significant mitochondrial separation between forms. Analysis indicated that the range of M. s. schreibersii in Turkey included Thrace and all coastal regions, whereas M. s. pallidus occupied the inland regions of central Anatolia. The results also pointed out to a significant difference in forearm lengths between M. s. schreibersii and M. s. pallidus. These forms might be distinct species, rather than subspecies, as they are recognized now.
Keywords: Bats -- Turkey.; Population genetics.